Biological treatment of palm oil mill effluent using Trichoderma viride - Abdul Karim, Mohamed Ismail; Ahmad Kamil, Ahmad Qalam (Elsevier BV, 1989)
Research was undertaken to investigate the treatment of palm oil mill effluent (POME) using the fungus Trichoderma viride to reduce its wastewater strength, and to recover the microbial mass. More than 95% reductin in Chemical Oxygen Demand (COD) of the POME was achieved after 10-14 days of fermentation. The fungal biomass produced from the POME was 1·37-1·42 g/litre (dry weight) of mycelium with a crude protein content of 37·6-40·7%.